2018
DOI: 10.1680/jgeot.16.t.028
|View full text |Cite
|
Sign up to set email alerts
|

Upper-bound solutions for face stability of circular tunnels in undrained clays

Abstract: The aim of this paper is to determine the critical supporting pressure on the circular face of an advancing tunnel in undrained clay in which undrained strength increases linearly with depth. Based on the kinematic approach of limit analysis, a continuous velocity field with a toric envelope is adopted to yield upper bounds of the face pressure for both collapse and blow-out. Combining with a closed-form expression describing the overall velocity field, an optimisation procedure is carried out to find the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…It is shown that the theoretical results derived by Equation (18) agree well with numerical results when H/D ≤ 3 but underestimate the tunnel stability when H/D = 5. It means the tunnel may not collapse when the plastic zone expands to the ground surface because of the arching effect, and some errors may also be induced from the simplified definition of k, as shown in Equation (19).…”
Section: Comparison Of Predicted Stability Numbers With Fela Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that the theoretical results derived by Equation (18) agree well with numerical results when H/D ≤ 3 but underestimate the tunnel stability when H/D = 5. It means the tunnel may not collapse when the plastic zone expands to the ground surface because of the arching effect, and some errors may also be induced from the simplified definition of k, as shown in Equation (19).…”
Section: Comparison Of Predicted Stability Numbers With Fela Resultsmentioning
confidence: 99%
“…, L/D ≥ 0.5 (19) and we chose this relationship mainly because there is only this equation available in the literature without losing simplification. Under the above assumptions, the 3D tunnel stability (L/D ≥ 0.5) can then be assessed by substituting Equation ( 19) into Equation (18).…”
Section: Assumptions and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…When a shallow tunnel is surrounded by weak rocks, insufficient supporting pressure or improper support will lead to collapse (active failure), while excessive supporting pressure will result in a blowout (passive failure) [1] . Current studies on the stability of shallow tunnels have made satisfactory progress, especially on the evaluation of the face stability [2][3][4][5] . Davis et al [3] evaluated the stability of shallow tunnels in a newly created failure mode by means of the upper and lower limit theorems of limit analysis.…”
Section: Introductionmentioning
confidence: 99%
“…e at-rest earth pressure coefficient K 0 is defined as the ratio of the effective horizontal stress versus vertical stress. It is a basic mechanic parameter of the soils in many practical engineering works such as slope [1] and tunnel [2] but is relatively difficult to determine. e mechanical properties of soil essentially depend upon the stress state, and therefore, accurate measurement of the initial stress state plays an important role in analyzing and designing the earthworks.…”
Section: Introductionmentioning
confidence: 99%